Fast Food: Gaya Hidup dan Promosi Makanan Siap Saji - Citra Rosalyn Anwar (Department Anthropology, Faculty of Social and Political Sciences Hasanuddin University., 2016)
As the capital city of South Sulawesi, Makassar’s economy has developed significantly. This is accompanied by mushrooming of food industry, such as catering, cafetaria and restaurant, including fast food restaurant, which can be seen from the increase number of such industry in many corners of the city. This article deals with how fast food restaurant has changed people’s life style and how such restaurant is promoted in various ways by different agents. Fast food restaurants have well developed—particularly in terms of variation of menu, taste, restaurant facilities, and services—and this has attracted many, including family and fast become ‘comfort food’ for its customers. People’s eating habit has changed, fast food reataurant is one of the pioneers of such change, from making fast food restaurant just as a dining area to become a place where people can eat and relax. Fast food restaurant was promoted not only by the restauran itself in various ways (i.e. advertisements, meal packages, payment methods in cooperation with certain banks, internal services, etc.), but also by the family from mother to children (and other members of the family and visa versa) through various occasion (i.e. eating out on the weekend, birthday party, arisan, etc.). The health information which concerning nutrition of fast food is poorly understood by the family. Despite the fact that nutrition and health aspects of fast food are considered, they are not really the primary matter of concern, reflecting the lack of awareness regarding nutricious and healthy food.